2014
DOI: 10.3906/sag-1212-3
|View full text |Cite
|
Sign up to set email alerts
|

Does lymph node involvement affect the patterns of recurrence in stage IB cervical cancer?

Abstract: IntroductionCarcinoma of the cervix uteri is the second most common cancer and the third most common cause of cancer deaths in women worldwide (1,2). The definitive primary treatment for patients with early-stage disease consists of radiation therapy or radical hysterectomy with pelvic and/ or paraaortic lymph node dissection (3). Knowledge about prognosis and recurrence is critical for the management of early-stage cervical cancer. Lymph node involvement is an important risk factor for recurrence in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
3
1
4
Order By: Relevance
“…Although better PFS was noted in the Rydzewska et al. study, no significant difference was seen in DFS between the two groups in the present study, and factors such as disease stage, lymph node metastasis, lymph node dissections and the number of dissected lymph nodes were related to cervical cancer prognosis . There was no doubt that patients with earlier disease stage have a better prognosis than those with later disease stages.…”
Section: Discussioncontrasting
confidence: 69%
“…Although better PFS was noted in the Rydzewska et al. study, no significant difference was seen in DFS between the two groups in the present study, and factors such as disease stage, lymph node metastasis, lymph node dissections and the number of dissected lymph nodes were related to cervical cancer prognosis . There was no doubt that patients with earlier disease stage have a better prognosis than those with later disease stages.…”
Section: Discussioncontrasting
confidence: 69%
“…Üreyen et al. reported on 27 early-stage CC patients with recurrence and found that lymph node invasion was significantly relevant to recurrence after surgical treatment ( 36 ). Another study by Mabuchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Even in early-stage CC, Tsunoda et al found that the incidence rate of lymph node metastasis ranges from 17-33% (35). Üreyen et al reported on 27 early-stage CC patients with recurrence and found that lymph node invasion was significantly relevant to recurrence after surgical treatment (36). Another study by Mabuchi et al revealed that it was the presence instead of the number and location of lymph node metastasis that independently affected the survival in patients with…”
Section: Discussionmentioning
confidence: 99%
“…Adanya metastasis KGB merupakan faktor risiko tinggi terjadinya kekambuhan pada karsinoma serviks stadium awal. 39 Usia pasien bervariasi antara 29 sampai 72 tahun, hal ini sejalan dengan hasil penelitian terdahulu, yang menyatakan bahwa Frekuensi usia kasus karsinoma serviks terbanyak yaitu pada kelompok usia 40-49 tahun, diikuti kelompok usia 50-59 tahun, hal ini sesuai dengan data Badan Registrasi Kanker Perhimpunan Dokter Spesialis Patologik Indonesia. 3,40 Pada hasil penelitian ini faktor-faktor risiko antara lain ukuran tumor, stadium klinis, jenis histopatologik, derajat diferensiasi, invasi limfovaskular dan invasi terdalam tidak dapat dinilai karena hasil pulasan sitokeratin AE1/AE3 pada seluruh kasus bulky KGB tidak ditemukan adanya mikrometastasis.…”
Section: Diskusiunclassified